Peran Tenaga Ahli Keuangan dalam Penguatan Studi Kelayakan Pendirian Rumah Sakit Umum Daerah di Kabupaten Semarang melalui Analisis Kelayakan Finansial - Suroto; Emiliana Sri Pujiarti; Agung Wibowo; Caecilia Sri Haryanti; Janti Soegiastuti; Andalan Tri Ratnawati (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2026)
A feasibility study is a critical stage in the planning of hospital establishment to ensure investment viability, particularly from a financial perspective. This community service program aims to provide reinforcement in the preparation of a feasibility study for the establishment of a Regional Public Hospital (RSUD) in Barukan Village, Tengaran District, Semarang Regency, through financial feasibility analysis conducted by financial experts. The implementation method was carried out through partner needs identification, delivery of financial analysis materials, interactive discussions, and assistance in developing financial models encompassing cash flow projections, discounted payback period (DPP), net present value (NPV), internal rate of return (IRR), and sensitivity analysis, all of which yielded feasible and acceptable results. The outcomes of the activity demonstrated an improvement in partners' understanding of financial feasibility analysis as well as their ability to interpret investment assessment criteria. In addition, the activity yielded an early-stage draft encompassing the financial feasibility aspects, which is intended to guide stakeholders in making informed decisions related to the founding of the Semarang Regency Regional Public Hospital. This activity contributes to strengthening the planning of healthcare facility investment in an effective and sustainable manner.